Pembangunan Sumberdaya Manusia oleh Struktur Perusahaan Jepang dan Indonesia di PT. KTI dan PT. RSI - Agastya Bhima Kumara Dewa; Hifdhul Haqqi Nazili Rohman; Robby Dwi Widiyanto (Pusat Riset dan Inovasi Nasional, 2023)
Developing human resources became important to support development programs. Indeed, what kind of human resources we should develop is it quality. It means, every person must to be get trained to gains skills in practicing profession wich is supporting the development programs. Condition when there is a gap between human resources quality and quantity surely became a problem in this process. When quantity of human resources increasing while it quality changeless or even decreasing, then the burden amount of human resources will be increased. The burdens are untrained human resources or a human resources without quality. Therefore, to re-enforce the development process, there must be a balance between quality and quantity of human resources. The development of human resources quality should be happen at companies which is employing people. Especially, on training period before people start to be a worker. Then the quality of human resources could be developed there in order to use all of those developed human resources quality to support development of country, or the Sustainable Development.